PELAKSANAAN RPP PADA PEMBELAJARAN TEMATIK DI MIS AL-IKWAH PONTIANAK - AZLANSYAH, Azlansyah (Jurnal Analisis Pendidikan Sosial, 2024)
This study aims to determine the suitability of the Learning Implementation Plan (RPP) with the implementation of Thematic teacher learning at MIS Al-Ikhwah Pontianak in classes V A, V B, and VI A. This research was conducted in December 2023. This research method is a qualitative descriptive method. Data collection techniques in this study were observation, interviews, and documentation. The results showed that in the implementation of the lesson plan (RPP) with learning was carried out with a percentage of 51.25%, including in the good category. While the second problem regarding the components of the Learning Implementation Plan made by the teacher consisting of 13 components is very good, based on the applicable 2013 Curriculum, with a percentage of 80%, and the results of the third problem research regarding the obstacles experienced in the implementation of the Learning Implementation Plan on Thematic learning at MIS Al-Ikhwah Pontianak related to the mismatch of time allocations, different characteristics of students and schools, and certain unexpected conditions.